Cочинения старообрядцев-беспоповцев в Речи Посполитой в XVIII в - Морозова, Надежда (Slavistica Vilnensis, 2013)
Статья посвящена творчеству староверов-беспоповцев Речи Посполитой в XVIII в. Сведения о тех или иных сочинениях, созданных польскими федосеевцами, появлялись в научной литературе еще в XIX в., однако они до сих пор не были систематизированы. Основное внимание в работе сосредоточено на творчестве Феодосия Васильева и его сына Евстрата Феодосиева (Феодосиевича), а также на текстах деяний федосеевских соборов, проходивших в Речи Посполитой в первой половине–середине XVIII в.Ключевые слова: староверие, Речь Посполитая, беспоповцы, федосеевские соборы, Феодосий Васильев, Евстрат Феодосиев....Nadezhda MorozovaWritings of priestless Old Believers in Polish–Lithuanian Commonwealth of the 18th century The article deals with the evaluation of creative works by priestless Old Believers residing in the Polish-Lithuanian Commonwealth in the 18th century. The study gives a special emphasis to the two main issues, i.e. 1) creative work of Feodosiy Vasilyev and his son Evstrat Feodosiyev (Feodosiyevich) and 2) the texts on activities of the Feodoseevtsy Council meetings that took place in the Polish–Lithuanian Commonwealth in the first half through the middle of the 18th century.The evaluation of the original creative work of priestless Old Believers of the Polish–Lithuanian Commonwealth specified in the article enables to conclude about the gradual expansion of the territories in which settlements of Old Believers appeared and the residents of which would be involved in active polemic and literary activities. The second third of the 18th century is characterized by the highest intellectual activity that would primarily be attributed to the inhabitants of the Sebezh lands.